Invasive Haemophilus influenzae type b infection in a patient with transient hypogammaglobulinemia of infancy. Issue 12 (December 2021) - Otaki, Yuji; Ogawa, Eiki; Higuchi, Toru; Takeshita, Kenichi; Takeuchi, Noriko; Ishiwada, Naruhiko; Ito, Kenta
Abstract: We describe a patient with invasive Haemophilus influenzae type b (Hib) infection despite being completely immunized by a conjugate Hib vaccine. Although Hib vaccination has contributed to significant reduction in invasive Hib infection, there are some case reports of invasive Hib infections despite immunization. I mmunoglobulin (Ig) deficiency is the main cause of primary vaccine failure, and IgG2 subclass deficiency is known to be the leading cause. A previously healthy 13-month-old boy visited the outpatient clinic with a 5-day history of fever (40.0 °C), cough, and vomiting, and was diagnosed with bacterial meningitis, purulent pericarditis, and arthritis. Hib was recovered from blood, cerebrospinal fluid, and pericardial fluid. Immunological examination revealed subnormal IgG and IgA titers at 13 and 17 months of age. Serum IgG2 titer was recovered at 17 months of age despite being low at 13 months. Comprehensive gene analysis for primary immunodeficiency syndromes (primary antibody deficiency, common variable immunodeficiency, and toll-like receptor abnormalities) were negative. The antibody titer against Hib [ anti -polyribosylribitol phosphate (PRP) antibody] was lower than the long-term protective titer (1.0 μg/ml) at 13 months of age, but was reactively increased to 2.38 μg/mL two months after booster immunization. Transient hypogammaglobulinemia of infancy (THI) is described as an accentuation and prolongation of the physiologic Ig nadir that is normally observed during infancy and defined as low IgG and IgA levels in the first three years of life. We speculate that he developed an invasive Hib infection as a result of primary Hib vaccine failure caused by THI. Graphical abstract: Table of Contents Summary : We describe a 13-month-old boy with invasive Haemophilus influenzae type b (Hib) infection despite being completely immunized with a conjugate Hib vaccine.